Ciências ambientais e interdisciplinaridade: estudo bibliométrico de teses em programas 6 e 7 - Cavalcanti, Daniele Belmont de Farias (Universidade Federal Rural do Semi-Árido, 2018)
The Environmental Sciences Department (CIAmb) in CAPES was created in 2011, in response to a question of environmental difficulty, due to the indissociability between anthropic and natural systems, so it is a multidisciplinary field of research that has interdisciplinarity and meaning of its existence. A discussion was started that emerged once the research presents the interdisciplinary perspectives foreseen in the Area Document? The questionnaire was introduced in the year 2017, considering the characteristics described in the Document of the Area: Environmental Sciences. This work is used methods of scientific methods and methods for an analysis of interdisciplinarity and creating the indicators of medical instruments and interdisciplinarity. The data were collected in the databases in 2000 and were not organized in MS Office Excel 2007, with the purpose of subsidizing a descriptive analysis and a Word Cloud Generator program for creating the word cloud. The results are demonstrated in an interdisciplinary way for the formation of a series of environmental, social and technological topics, required for a science area, and are present in the CAPES graduate programs 6 and 7, of a certain concentration of subjects and formations of egresses, mentors and curators in certain institutions, as well as the theses should contemplate more the use of the technologies in their researches, for the better or more interdisciplinary of integration social-social-technology. This work was based on the subsidies for a more efficient management of the CAPES programs 6 and 7, and the old resistance with these programs that included an evaluation of the interdisciplinary characteristics was also collaborated for other programs inserted in the CiAmb. interdisciplinary evidence in the theses of the Environmental Sciences area, as it is fundamental and fundamental about the area of qualifications, as well as identified some opportunities for improvement in some aspects such as the development of research that integrate the most technical issues, The areas that are originated in the area of Environmental Sciences are being reached in full and in an excellent way
Keywords: Ciências ambientais; Interdisciplinaridade; Bibliometria; Environmental sciences; Interdisciplinarity; Bibliometry; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE